Counting, analysing and reporting exacerbations of COPD in randomised controlled trials. Issue 2 (16th August 2007) - Aaron, S D; Fergusson, D; Marks, G B; Suissa, S; Vandemheen, K L; Doucette, S; Maltais, F; Bourbeau, J F; Goldstein, R S; Balter, M; O'Donnell, D; FitzGerald, M
Abstract : Background: Clinical trials measure exacerbations of chronic obstructive pulmonary disease (COPD) inconsistently. A study was undertaken to determine if different methods for ascertaining and analysing COPD exacerbations lead to biased estimates of treatment effects. Methods: Information on the methods used to count, analyse and report COPD exacerbation rates was abstracted from clinical trials of long-acting bronchodilators or long-acting bronchodilator/inhaled steroid combination products published between 2000 and 2006. Data from the Canadian Optimal Therapy of COPD Trial was used to illustrate how different analytical approaches can affect the estimate of exacerbation rates and their confidence intervals. Results: 22 trials (17 156 patients) met the inclusion criteria and were reviewed. None of the trials adjudicated exacerbations or determined independence of events. 14/22 studies (64%) introduced selection bias by not analysing outcome data for subjects who prematurely stopped study medications. Only 31% of trials used time-weighted analyses to calculate the mean number of exacerbations/patient-year and only 15% accounted for between-subject variation. In the Canadian Optimal Therapy of COPD Trial the rate ratio for exacerbations/patient-year was 0.85 when all data were included in a time-weighted analysis, but was overestimated as 0.79 when data for those who prematurely stopped study medications were excluded and was further overestimated as 0.46 when a time-weighted analysis was not conducted; p values ranged from 0.03 to 0.24 depending on how exacerbations were determined and analysed. Conclusions: Clinical trials have used widely different methods to define and analyse COPD exacerbations and this can lead to biased estimates of treatment effects. Future trials should strive to include blinded adjudication and assessment of the independence of exacerbation events, and trials should report time-weighted intention-to-treat analyses with adjustments for between-subject variation in COPD exacerbations.